2021
DOI: 10.1017/s1041610221000363
|View full text |Cite
|
Sign up to set email alerts
|

Applying generalizability theory to examine assessments of subjective cognitive complaints: whose reports should we rely on – participant versus informant?

Abstract: Objectives: This study aimed to apply the generalizability theory (G-theory) to investigate dynamic and enduring patterns of subjective cognitive complaints (SCC), and reliability of two widely used SCC assessment tools. Design: G-theory was applied to assessment scales using longitudinal measurement design with five assessments spanning 10 years of follow-up. Setting: Community-dwelling older adults aged 70–90 years and their informants, living in Sydney, Australia, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…In conclusion, there is growing recognition of the utility and limitations of self-and informantreported SCCs in identifying those who may be at risk of developing objective declines in the future. The work by Truong et al (2022) adds support for the potential utility of SCCs when measured by reliable and generalizable measures. Their findings and the extant literature suggest that both self-and other-reported SCCs can be important parts of a comprehensive, integrated assessment of an older adult's cognitive and mental health status.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In conclusion, there is growing recognition of the utility and limitations of self-and informantreported SCCs in identifying those who may be at risk of developing objective declines in the future. The work by Truong et al (2022) adds support for the potential utility of SCCs when measured by reliable and generalizable measures. Their findings and the extant literature suggest that both self-and other-reported SCCs can be important parts of a comprehensive, integrated assessment of an older adult's cognitive and mental health status.…”
mentioning
confidence: 79%
“…The study by Truong et al (2022) expands the existing body of SCC literature by evaluating dynamic and enduring patterns of SCCs reported by patients and informants over a 10-year span. In a large sample of community-dwelling older adults from Australia, the authors used generalizability theory to examine the overall reliability of two widely used measures of self-and informant-reported SCCsthe Memory Complaint Questionnaire (MAC-Q) and the Informant Questionnaire on Cognitive Decline in the Elderly (IQ-CODE).…”
mentioning
confidence: 99%
“…13 Results from the MAS showed that informant IQCODE scores were more accurate in predicting cognitive performance and incident dementia compared to self-reported MAC-Q scores. 5 Moreover, self-reports are subject to various biases such as the individual's mood (e.g. depression, anxiety), personality traits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Generalizability theory (G theory) is an advanced statistical method that estimates all possible error variances and their influences on the overall reliability of a measure (Truong et al, 2020(Truong et al, , 2021. G theory is increasingly being used to investigate the psychometric properties of measurement tools and to distinguish dynamic and enduring symptoms.…”
mentioning
confidence: 99%